MiR24–3p activity after delivery into pancreatic carcinoma cell lines exerts profound tumor-inhibitory effects through distinct pathways of apoptosis and autophagy induction. (10th April 2021) - Borchardt, Hannes; Ewe, Alexander; Morawski, Markus; Weirauch, Ulrike; Aigner, Achim
Abstract: Pancreatic cancer is among the most detrimental tumors, with novel treatment options urgently needed. The pathological downregulation of a miRNA in tumors can lead to the overexpression of oncogenes, thus suggesting miRNA replacement as novel strategy in cancer therapy. While the role of miR24 in cancer, including pancreatic carcinoma, has been described as ambiguous, it may hold great promise and deserves further studies. Here, we comprehensively analyze the effects of miR24–3p replacement in a set of pancreatic carcinoma cell lines. Transfection of miR24–3p mimics leads to profound cell inhibition in various 2D and 3D cell assays, based on the induction of apoptosis, autophagy and ROS. Comprehensive analyses of miR24–3p effects on the molecular level reveal the transcriptional regulation of several important oncogenes and oncogenic pathways. Based on these findings, miRNA replacement therapy was preclinically explored by treating tumor xenograft-bearing mice with miR24–3p mimics formulated in polymeric nanoparticles. The obtained tumor inhibition was associated with the induction of apoptosis and necrosis. Taken together, we identify miR24–3p as powerful tumor-inhibitory miRNA for replacement therapy, and describe a complex network of oncogenic pathways affected by miR24. Highlights: Transfection of miR24–3p mimics leads to profound cell inhibition, based on apoptosis, autophagy and ROS induction. Transcriptional regulation of several important oncogenes and oncogenic pathways is observed upon miR24–3p replacement. MiRNA replacement therapy in tumor xenograft-bearing mice reveals tumor inhibition, induction of apoptosis and necrosis. MiR24–3p is a powerful tumor-inhibitory miRNA, based on affecting a complex network of oncogenic pathways.